Extramural educational institutionsas an institution of socialization at the senior age of adolescences - Sviatoho, H. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
This article presents the characteristics of adolescence, the most significant in terms of social development of the individual. The main differences between extra curriculum and formal educational environment which act as necessary psychological and pedagogical conditions of formation and social development of the identity in adolescence are described.